Cardiac Autonomic Dysfunction: Particulate Air Pollution Effects Are Modulated by Epigenetic Immunoregulation of Toll‐like Receptor 2 and Dietary Flavonoid Intake. Issue 1 (27th January 2015) - Zhong, Jia; Colicino, Elena; Lin, Xinyi; Mehta, Amar; Kloog, Itai; Zanobetti, Antonella; Byun, Hyang‐Min; Bind, Marie‐Abèle; Cantone, Laura; Prada, Diddier; Tarantini, Letizia; Trevisi, Letizia; et al.
Abstract : Background: Short‐term fine particles (PM2.5 ) exposure is associated with reduced heart rate variability, a strong predictor of cardiac mortality among older people. Identifying modifiable factors that confer susceptibility is essential for intervention. We evaluated whether Toll‐like receptor 2 ( TLR2 ) methylation, a reversible immune‐epigenetic process, and its dietary modulation by flavonoids and methyl nutrients, modify susceptibility to heart rate variability effects following PM2.5 exposure. Methods and Results: We measured heart rate variability and PM2.5 repeatedly over 11 years (1275 total observations) among 573 elderly men from the Normative Aging Study. Blood TLR2 methylation was analyzed using pyrosequencing. Daily flavonoid and methyl nutrients intakes were assessed through the Food Frequency Questionnaire (FFQ). Every 10 μg/m 3 increase in 48‐hour PM2.5 moving average was associated with 7.74% (95% CI: −1.21% to 15.90%; P =0.09), 7.46% (95% CI: 0.99% to 13.50%; P =0.02), 14.18% (95% CI: 1.14% to 25.49%; P =0.03), and 12.94% (95% CI: −2.36% to 25.96%; P =0.09) reductions in root mean square of successive differences, standard deviation of normal‐to‐normal intervals, low‐frequency power, and high‐frequency power, respectively. Higher TLR2 methylation exacerbated the root mean square of successive differences, standard deviation of normal‐to‐normal intervals, low‐frequency, and high‐frequency reductions associated with heightened PM2.5 ( P interaction =0.006, 0.03, 0.05, 0.04, respectively). Every interquartile‐range increase in flavonoid intake was associated with 5.09% reduction in mean TLR2 methylation (95% CI: 0.12% to 10.06%; P =0.05) and counteracted the effects of PM2.5 on low frequency ( P interaction =0.05). No significant effect of methyl nutrients on TLR2 methylation was observed. Conclusions: Higher TLR2 methylation may confer susceptibility to adverse cardiac autonomic effects of PM2.5 exposure in older individuals. Higher flavonoid intake may attenuate these effects, possibly by decreasing TLR2 methylation.